Management of chronic wasting disease in ranched elk: conclusions from a longitudinal three-year study. Issue 1 (1st January 2020) - Haley, N.J.; Henderson, D.M.; Donner, R.; Wyckoff, S.; Merrett, K.; Tennant, J; Hoover, E.A.; Love, D.; Kline, E.; Lehmkuhl, A.D.; Thomsen, B.V.
ABSTRACT: Chronic wasting disease is a fatal, horizontally transmissible prion disease of cervid species that has been reported in free-ranging and farmed animals in North America, Scandinavia, and Korea. Like other prion diseases, CWD susceptibility is partly dependent on the sequence of the prion protein encoded by the host's PRNP gene; it is unknown if variations in PRNP have any meaningful effects on other aspects of health. Conventional diagnosis of CWD relies on ELISA or IHC testing of samples collected post-mortem, with recent efforts focused on antemortem testing approaches. We report on the conclusions of a study evaluating the role of antemortem testing of rectal biopsies collected from over 570 elk in a privately managed herd, and the results of both an amplification assay (RT-QuIC) and conventional IHC among animals with a several PRNP genotypes. Links between PRNP genotype and potential markers of evolutionary fitness, including pregnancy rates, body condition, and annual return rates were also examined. We found that the RT-QuIC assay identified significantly more CWD positive animals than conventional IHC across the course of the study, and was less affected by factors known to influence IHC sensitivity – including follicle count and PRNP genotype. We also found that several evolutionary markers of fitness were not adversely correlated with specific PRNP genotypes. While the financial burden of the disease in this herd was ultimately unsustainable for the herd owners, our scientific findings and the hurdles encountered will assist future CWD management strategies in both wild and farmed elk and deer.